1979
DOI: 10.1152/ajpheart.1979.237.1.h59
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular myogenic reaction in the wing of the intact unanesthetized bat

Abstract: Microvascular dimension and flow responses to stepwise changes in arterial and venous pressures, ranging from zero to +100 mmHg and zero to -75 mmHg have been recorded. Observations were made in arterioles, terminal arterioles, and precapillary sphincters in the wing web of intact, unanesthetized bats. The results show for all categories of vessels that with reduced transmural pressures there is a progressive increase in mean diameter and a decrease in rhythmic vasomotion rate. Flow changes are variable. For e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
1

Year Published

1981
1981
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…At ambient pressures of ±20 mm Hg, vessel wall tension typically remained within ±10-15% of control. At ambient pressures of ±25 mm Hg, Bouskela and Wiederhielm (1979) calculated that the wall tension remained within -32% to +28% of control, which is somewhat greater than found in the present study for a similar range of ambient pressures. Mesenteric arterioles which constricted as intravascular pressure was increased, in the study by Burrows and Johnson (1983), demonstrated only a 3.8% increase in wall tension for a 10% pressure increase.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…At ambient pressures of ±20 mm Hg, vessel wall tension typically remained within ±10-15% of control. At ambient pressures of ±25 mm Hg, Bouskela and Wiederhielm (1979) calculated that the wall tension remained within -32% to +28% of control, which is somewhat greater than found in the present study for a similar range of ambient pressures. Mesenteric arterioles which constricted as intravascular pressure was increased, in the study by Burrows and Johnson (1983), demonstrated only a 3.8% increase in wall tension for a 10% pressure increase.…”
Section: Discussioncontrasting
confidence: 56%
“…Vessel wall tension at a nearly constant diameter would essentially be a direct function of transmural pressure and, as such, a sustained stimulus for a myogenic response. Such a situation has been observed by Bouskela and Wiederhielm (1979) for bat arterioles at ambient pressures of ±25 mm Hg and by Dacey and Duling (1982) for isolated arterioles of the rat cerebral cortex. The potential for sustained myogenic responses has been recently reviewed by Johnson (1980).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Bouskela and Wiederhielm 64 found that the constriction of arterioles and precapillary sphincters in the bat wing tended to maintain calculated wall tension constant during simultaneous elevation of arterial and venous pressures. Burrows and Johnson 72 found that as arterial pressure to the cat mesentery was reduced, arteriolar dilation tended to maintain wall tension.…”
mentioning
confidence: 99%
“…It is not clear why increases in transmural pressure rarely enhanced constriction of these isolated blood vessels in contrast to arterioles in vivo (Bouskela & Wiederhielm, 1979; Borgstr6m, Grande & Lindbom, 1981;Burrows & Johnson, 1981;Morff & Granger, 1982). This difference between blood vessels in vivo and in vitro may, in part, reflect differences in activation of the muscle or in stress on the muscle.…”
Section: Discussionmentioning
confidence: 99%